Textile paths:: possibilities of creative routes in the female context (Palíndromo, 2021)
Revisiting the modern values that refer to the role of the artist and his actions, the article proposes to analyze the difficulties experienced by women in relation to the access of the public space and the gesture of composing trajectories through it. It is suggested that the textile media provided a means of creative journey that recognizes the self and the home environment as a landscape to be appropriated and built.
Keywords: Textiles.; Feminism.; Trajectories.; Modernity.; Contemporary.